Transport Accessibility as Merit Good - Francesca Medda (European Regional Science Association (ERSA), 2010)
The individual's perception of transport cost usually does not include the full social cost of transport, as in for instance, its global environmental effects. Under this view, we observe a mismatch between individual perception and general social transport cost and welfare. In order to overcome this paradox, we need to induce a shift from the limited individualistic perspective to a more socio-economic view, whereby ethical judgments play a role in the economic decision-making process. Transport accessibility is here examined as a merit good and we therefore assume the necessity for government intervention in its provision. However, transport accessibility may be achieved through different levels of merit good values, as for instance, rail intervention versus road intervention. Some transport systems achieve greater fairness in accessibility, thus a higher merit good value; this implies that social planners need to discriminate various levels of subsidy and investment in relation to the fairness in transport accessibility.
Keywords: H20; R40; 330; transport; accessibility; merit goods